Virtual museums and built environment: narratives and immersive experience via multi-temporal geodata hub - Raffaella Brumana; Daniela Oreni; Sara Caspani; Mattia Previtali (Virtual Archaeology Review)
Our  built environment  is  nowadays considered as a  dynamic complex,  stretching  and  transforming  across  space  and time, with the interaction of human, social and economic dimensions. It needs to be safeguarded as living places for the future taking into account such complexity.  The  general aim  of  this  work  is  to  contribute  to  the comprehension of landscape   values,   enhancing   participation   processes   by   tourists and   local communities, considering the   built environment as a system: the sum of natural transformation, ancient artefacts stratification and human activities, partially covering  the  tangible  traces, and  functioning  as  a vehicle for  the  comprehension  of  intangible  values. Multi-temporal, multi-scale and geospatial datasets can play an important role in such knowledge transfer processes by means of narratives and immersive experiences in a multimedia museum approach. In particular, the cartographic  heritage, in the form  of  metric  and non-metric maps, can  be  progressively  used as  a source  of  information for  innovative  narratives. Virtual  Museums  (VMs)are  additional  "channels" to  disseminate content  and to  provide knowledge  about  cultural heritage; they have emerged from the crossbreeding process between museums and digital technologies. Investigating how  digital  storytelling  may  support  communication  and  understanding  of  complex  systems,  such  as  the  built environment  and  landscape, it  is relevant because cultural  awareness  may foster the sense of  belonging  and  identity construction of  which  Europe  is  thirsty,  contributing  to  the  safeguarding of  fragile  sites. The paper provides useful information for museums that would like to follow this pathway. It retraces the main steps of storytelling production and presents interesting examples of immersive narrative models based on geospatial data and a virtual hub, helping people to retrieve and access information and to recognize places of memory mostly unknown. Moreover, it offers an evaluation of existing tools that can be adopted for this purpose. Eventually, by virtue of the research carried out for the case study of the Virtual Museum of Como Lake Landscape, the paper aims at ascertaining which kind of stories and experiences can be designed, the potential of these tools and possible weaknesses or constraints that deserve future researches.